Impact of road- and vehicle-related parameters on the energy efficiency of hybrid city buses. (2015) - Balters, Stephanie; Scholz-Starke, Kai; Eckstein, Lutz
Owing to a reduction of energy consumption along with a decrease of pollutant gaseous and noise emissions, hybrid power train topologies have a high potential as eco-friendly and cost-efficient propulsion technology. The aim of this study is therefore to identify vehicle- and road-related parameters of hybrid city buses and to examine their impact on energy consumption. For this purpose an energy analysis of selected parameters, which affect the operation of public transport buses, namely bus stops, traffic signal priority, bus lanes, traffic density, and passenger load profile, is undertaken. Based on a mathematical model, the impact parameters can be quantified and their impact on energy consumption is measured with the aid of the simulation tool Matlab/Simulink. The consumption share of each parameter is analysed. With this methodology the potential savings of hybrid buses under urban traffic conditions through novel operating strategies can be identified.